Innovation of Educational Institutions in the Millennial Era - Iman Haqiqi, Zulfikar Abdulah (International Conference of Moslem Society, 2019)
The rapid development of the times now brings us to positive and negative developments in the lives of all people including in education management. educational institutions besides being able to present innovation while ensuring the quality of their students are not left behind by the times. The term millennial that is inherent in this era is inseparable from technological advances that are so fast that it needs good management that does not seem old-fashioned and lagging so as to foster a high interest in learning among students while achieving the vision and mission of the institution. Innovations in educational institutions include curriculum innovation, technological innovation, learning innovation, and learning media innovation so that educational institutions and educational devices can compete to achieve the best goals and results for the Indonesian people.